Praktik Ketubuhan Silek Dalam Silek Galombang Binuang Sati Dan Tari Pasambahan Syofyani - Shindi Lara Sati; Rustim Rustim; Ediwar Ediwar (SENDRATASIK UNP, 2022)
This study aims to reveal the practice of silek in the formation of the performing arts of Silek Galombang Binuang Sati and Syofyani's Pasambahan Dance as well as the silek body that is presented in the two performing arts. This research is expected to add references and knowledge about traditional dances that grow and develop in the archipelago, and can find the role of Silek in a performance. The discussion is focused on embodiment analysis which emphasizes on performance or often known as a performance-centered approach. Embodiment includes the body of the performer involved in the performing arts. The results of the study show that overall the two performances have different bodily experiences, even though they come from the same body (embodiment).